Akuntansi dan Pengelolaan Keuangan Berbasis Komputer bagi Kepala Sekolah Penerima Dana BOS di Kota Bandar Lampung - Kurniawan Saputra; - Nurmala (Jurnal Informatika, 2010)
The increase in unit cost of BOS in the year 2009 is significant evidence of government commitment in carrying out the mandate of the Constitution regarding the 20% budget for education. The commitment of this government must also be followed by increased government commitment and community participation in monitoring programs and funding. Based on this, the in-depth knowledge of Microsoft Office is required by the school principal and the school treasurer. It is necessary to an understanding of Microsoft Office that includes: Ms Excel. The aim is for school principals and treasurers to process data based computer applications in accounting / finance, especially financial management BOS to BOS with the orderly administration implemented, transparent, accountable, efficient, timely, and avoid deviations. Keyword :Accounting, BOS